The Concept of Separation of Power in Indonesia Al-Zuhaili Priest Perspective - Rahmat Rahmat (Journal of Economic and Islamic Research, 2023)
Indonesia is one of the countries that adheres to the trias politica power separation system, the concept that is the reference to the power separation system in Indonesia has in common with the trias politica offered by John Jock who divides power into the legislative, executive and judiciary. But over time there is a group of people who say that the government system implemented in Indonesia is a pagan government system. And this opinion is indisputable because there are scholars 'who have the concept of separation of powers which is exactly the system of separation of powers in Indonesia, namely Wahbah al Zuhaili he divides power into legislative power (sultatu al-tasri’i), executive (sultatu al-tanfidhi) and the judiciary (sultatu al-qodo’i). This type of research is a normative legal research using two approaches: a comparative approach and a conceptual approach. The primary legal source is Fiqhu al-Islam Wa Adillatuhu, Restoration of Indonesian Constitutional Law Based on the 1945 Constitution, secondary legal sources are books and other scientific works related to the object of discussion in this study. The results of this study conclude: First, Indonesia adheres to the power separation system of trias politica by dividing the three powers, the legislature, the executive and the judiciary. Secondly, in the Islamic system of government there is also the term separation of powers which also divides the types of power that is, sultatu al-tasri’i', sultatu al-tanfidhi, sultatu al-qodo’i. Third, the Indonesian state in applying the separation of powers has similarities with the Islamic governance system from Wahbah al-Zuhaili's perspective, so that it answers that the Indonesian state in its government system does not adhere to a kafi government system